The Permissibility of Limiting Rights and Freedoms in the European and National Legal System Due to Health Protection - Tabaszewski, Robert Krzysztof (Review of European and Comparative Law, 2020)
The article concerns the permissibility of limiting human rights and freedoms in European and national systems due to the protection of individual and public health. The author's goal was to analyse the current practice of states in the application of human rights limitation clauses in the European system of human rights protection. This is an important issue because the practice of limitation and margin of appreciation enjoyed by the member states of the Council of Europe is subject to scrutiny by means of complaints addressed to the European Court of Human Rights in Strasbourg, which examines the correct application of individual limitation clauses contained in the 1950 Convention. Human health is one of the main prerequisites for which it is possible to limit other human rights and freedoms. In the context of numerous epidemiological threats and natural disasters of a cross-border nature, assessing rights and freedoms becomes one of the most important issues in the field of public international law, constitutional law and public health law. Against the background of existing solutions in the universal system, the practice of the member states of the European Union and the Council of Europe was examined by comparing it with the views of the doctrine and the results of my research.